Expression of aberrant markers in monitoring of measurable residual disease in B-cell precursor acute lymphoblastic leukemia patients during remission-inducing therapy phase - Słota, Ł.; Sędek, Ł.; Lejman, M.; Perkowski, B.; Lasia, A.; Bulsa, J.; Młynarski, W.; Kowalczyk, J.; Szczepański, T. (Frontiers in Oncology, 2025)
IntroductionB-cell acute lymphoblastic leukemia (BCP-ALL) is characterized by an abnormal proliferation of immature cells in bone marrow. Leukemic blasts at diagnosis exhibit a so-called leukemia associated immunophenotype (LAIP), which is further used for determination of measurable residual disease (MRD) levels at particular time points during the therapy. Nevertheless, in some patients LAIP proves insufficient for discrimination of blasts from their normal counterparts, therefore, search for novel, aberrant markers is essential. A crucial requirement for these antigens is their expression variability throughout the entire treatment monitoring period.MethodsThe aim of the study was to assess the expression level of four markers: CD66c, CD304, CD72 and CD86 on leukemic cells at diagnosis and at day 15 and 33 of treatment to compare stability of their expression. We also correlated the results obtained with the most common genetic aberrations identified at the diagnosis of BCP-ALL, such as: hyper- hypodiploidy, BCR::ABL1, KMT2A::AFF1, ETV6::RUNX1, TCF3-rearangement, TCF3::PBX1, TCF3::HLF, KMT2A and IKZF1 mutations.ResultsIn more than 90% of patients, CD86 overexpression on blast cells was proven at day 15 of treatment and in almost 93% during the entire remission-inducting therapy (day 33). Similarly high positivity rate on leukemic blasts was found for CD72 antigen, which at day 15 was positive in 82% of patients and dropped to 43% at day 33 of treatment. We also found a correlation between the presence of hyperdiploidy and ETV6::RUNX1 and changes in the expression of particular markers.DiscussionThe obtained results demonstrate that CD86 and CD72 can be successfully used as additional markers for MRD assessment in BCP-ALL.